2015
DOI: 10.16943/ptinsa/2015/v81i5/48333
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse Gas Emission fromIndian Agriculture: Trends, Drivers and Mitigation Strategies

Abstract: Climate change, caused by the increase in concentrations of greenhouse gases (GHGs) in the atmosphere, has emerged as the most prominent environmental issue all over the world. It will have a considerable impact on agriculture including crops, livestock and fisheries. Agriculture, crucial for ensuring food, nutritional and livelihood security of India, is exposed to the stresses arising from climatic variability and climate change. Agriculture sector is also a major contributor to the enhanced greenhouse effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 12 publications
2
29
0
Order By: Relevance
“…from cropland. The GHG emission from methane (Metric ton) reported in India in the rice field varies significantly from 3.3 to 37.5 as per the report of various scientists (Pathak et al, 2014). Hou et al (2012) also found similar observation where they found various agro-ecosystems plays a significant role in the GHG emission.…”
Section: The Analysis Of Agro-ecological Regionsmentioning
confidence: 58%
“…from cropland. The GHG emission from methane (Metric ton) reported in India in the rice field varies significantly from 3.3 to 37.5 as per the report of various scientists (Pathak et al, 2014). Hou et al (2012) also found similar observation where they found various agro-ecosystems plays a significant role in the GHG emission.…”
Section: The Analysis Of Agro-ecological Regionsmentioning
confidence: 58%
“…Several studies reported that PTR produces more CH4 emissions than DSR, while DSR produces more N2O than PTR [3]. In one study, DSR and PTR produced N2O emissions of 1.2 t CO2eq ha -1 and 0.4 t CO2eq ha -1 , respectively and CH4 emissions of 0.1 t CO2eq ha -1 and 0.6 t CO2eq ha -1 , respectively [42]. In conclusion, the adoption of monocultures in RWCS contributes to global GHG emissions due to intensive agricultural inputs use and residue burning.…”
Section: Greenhouse Gas Emissionsmentioning
confidence: 99%
“…In the current study, there was a significant reduction in total GHG emission in DSR (574.1 kg CO 2 equivalent) versus the PTR system (3954.8 kg CO 2 equivalent). Pathak [53] reported that continuous flooding, nitrogen fertilizers and machinery are responsible for the higher GHG emissions from PTR farms. Puddling and continuous flooding of rice fields encourages the activity of methanogenesis, thereby increasing methane emission.…”
Section: Greenhouse Gas (Ghg) Emissionmentioning
confidence: 99%